2015
DOI: 10.5812/ircmj.16640
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Depression During Pregnancy and the Correlation Between Social Support and Pregnancy Depression

Abstract: Background:Women are seriously subjected to psychiatric diseases during pregnancy and depression is the most prevailing one among these diseases. There is a relation between the social support and depression in pregnancy whose predisposing factors are genetic, psychological, biological, environmental, and hormonal.Objectives:This study aimed to determine the frequency of depression symptoms, and its risk factors. Also it studied the correlation between social support and pregnancy depression.Patients and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 32 publications
7
42
1
11
Order By: Relevance
“…Gearing, McNeill and Lozier (2005) argue that a fundamentally important, but frequently minimised and ignored factor, is the role of fathers in the issue of FASD. Lack of paternal involvement is associated with an increase in the use of alcohol (Aktas & Calik, 2015), as well as maternal depressive symptoms and emotional distress that may feed into alcohol use (Nduna & Jewkes, 2012). A recent South African literature review demonstrated that women's relative disempowerment in relationships with men reinforce unequal positions in families, societies and public domains (Fladseth, Gafos, Newell & McGrath, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Gearing, McNeill and Lozier (2005) argue that a fundamentally important, but frequently minimised and ignored factor, is the role of fathers in the issue of FASD. Lack of paternal involvement is associated with an increase in the use of alcohol (Aktas & Calik, 2015), as well as maternal depressive symptoms and emotional distress that may feed into alcohol use (Nduna & Jewkes, 2012). A recent South African literature review demonstrated that women's relative disempowerment in relationships with men reinforce unequal positions in families, societies and public domains (Fladseth, Gafos, Newell & McGrath, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In studies that investigated the rates of depression in different cultures, the rate of depression during pregnancy was found to be 7.5% in China, 17.9% in Hungary, 30% in Canada, 19.6% in the USA and 19.6% in Brazil, whereas in Turkey it ranges from 12% to 36% (Aktas et al 2015). According to Park et al (2015) the prevalence of depression in the prenatal and postpartum period in Korean women ranged from 40.5% to 61.4 %.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported the prevalence of stress and anxiety during pregnancy as 6% to 78%; that is, 6% of the population is reportedly exposed to high levels of stress and 78% is exposed to low or moderate levels (7)(8)(9). Stress during pregnancy can be associated with adverse pregnancy outcomes such as miscarriage, fetal weight loss, increased stress hormone levels, chronic hypertension, premature birth, infant mortality, changes in endocrine secretion, changes in hypothalamic-pituitary function, suppressed immune system, changes in the number of lymphocytes and reduced CD4/CD8 ratio, nausea, vomiting, preeclampsia, and some degree of mental disorder (10)(11)(12)(13)(14)(15)(16). The complications associated with pregnancy-induced stress are a leading cause of maternal perinatal mortality (17).…”
Section: Introductionmentioning
confidence: 99%